2019 34th IEEE/ACM International Conference on Automated Software Engineering (ASE) 2019
DOI: 10.1109/ase.2019.00069
|View full text |Cite
|
Sign up to set email alerts
|

Demystifying Application Performance Management Libraries for Android

Abstract: Being able to automatically detect the performance issues in apps can significantly improve apps' quality as well as having a positive influence on user satisfaction. Application Performance Management (APM) libraries are used to locate the apps' performance bottleneck, monitor their behaviors at runtime, and identify potential security risks. Although app developers have been exploiting application performance management (APM) tools to capture these potential performance issues, most of them do not fully unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 43 publications
(71 reference statements)
0
5
0
Order By: Relevance
“…According to Android permission mechanism, TPLs share the same privileges with host apps [19]- [21]. TPLs may abuse permissions to access users' personally identifiable information without users' consent [22], [23], which results in personal information leakage [8]- [18], [53].…”
Section: A Android Third-party Librariesmentioning
confidence: 99%
“…According to Android permission mechanism, TPLs share the same privileges with host apps [19]- [21]. TPLs may abuse permissions to access users' personally identifiable information without users' consent [22], [23], which results in personal information leakage [8]- [18], [53].…”
Section: A Android Third-party Librariesmentioning
confidence: 99%
“…Due to Android's permission mechanism, TPLs share the same privileges with host apps [19]- [21]. TPLs may abuse permissions to access users' personally identifiable information without users' consent [22], [23], which results in personal information leakage [8]- [18], [53].…”
Section: Background a Android Third-party Librariesmentioning
confidence: 99%
“…Some of the mobile analytics tools focus on monitoring performance of the software [37], [38]. A recent study found mobile analytics are often used poorly and with user-privacy concerns [17].…”
Section: Related Workmentioning
confidence: 99%
“…For example, mobile analytics logging may bring extra non-negligible resource overhead to generate and transmit the logs. In addition, the remote storage of information may also bring privacy concerns [17]. Therefore, research into the characteristics of practices of mobile analytics logging is germane to help practitioners and researchers further understand and address the challenges.…”
Section: Introductionmentioning
confidence: 99%